Lao People's Democratic Republic : 2009 Article IV Consultation; Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2009)
Lao People's Democratic Republic's growth is expected to moderate but remain fairly robust, supported by large projects in train, strong mineral exports, and expansionary policies. The staff report for the Lao People's Democratic Republic's 2009 Article IV Consultation highlights economic developments and policies. The largest impact has been on the mining sector, but delays in hydropower projects are also evident. Inflation is expected to remain low and stable, assuming no significant pickup in commodity prices. However, overly expansionary fiscal and credit policies pose a risk to macroeconomic stability.